KEPUTUSAN MAHASISWA MEMILIH TEMPAT INDEKOS DI MAMUJU: FOCUSED GROUP DISCUSSION DENGAN MAHASISWA JURUSAN MANAJEMEN STIE MUHAMMADIYAH MAMUJU - Nugraha, Shafwan (LPPM Universitas Muhammadiyah Mamuju, 2019)
Recently in Mamuju, many boarding houses appeared. The more students come from out of Mamuju Subdistrict area means more demand on the availability of boarding rooms. However, the abundant choices of boarding rooms and places means students as prospective consumers must consider several criterias before deciding which boarding place they rent. This research is an explorative research conducted with qualitative methodology. Data for this research was acquired using focused group discussion (FGD) method. The acquired data was triangulated with results of questionnaire shared among respondents that different from the participants of FGD session. The source of the data are students of Management Departement at Sekolah Tinggi Ilmu Ekonomi Muhammadiyah class of 2019. The result of the research revealed that security, comfort, facility offered, rent price, distance to campus, distance to food and ingredients shop, distance to everyday needs shop, and distance to other public facilities are the consideration criterias used by the students on choosing boarding place. Security criteria is the most important to consider, while rent price criteria is the least important one